2020
DOI: 10.46912/jbrcp.193
|View full text |Cite
|
Sign up to set email alerts
|

Chronic High Fat Diet Induced Weight Gain, Hyperglycaemia and Cognitive Impairment in Albino Mice

Abstract: With the global rise in consumption of western diet, obesity is becoming a pandemic. High fat and high calorie diet (though more palatable) have been associated with a range of metabolic disorders. Oxidative stress and insulin resistance have a link to the dietary etiology of diabetes and obesity; on the other hand, neuroinflammation and abnormal brain insulin signaling is said to cause cognitive decline when high fat diet (HFD) is consumed. In this study, mice were fed a home-made HFD with a total energy cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 1 publication
(1 reference statement)
1
3
0
Order By: Relevance
“…The groups allowed high fat diets (diabetic groups) had significantly higher blood glucose levels compared with the control and gliclazide groups. These differences in glucose level could be as a result of increased dietary intake (high fat diet), which often leads to obesity, insulin resistance and hyperglycaemia, as previously reported ( Lang et al, 2019 , Abi et al, 2020 ). There were further significantly increased blood glucose levels in the diabetic groups after induction with streptozotocin compared with the control and gliclazide groups, an indication that streptozotocin exacerbates hyperglycaemia.…”
Section: Discussionsupporting
confidence: 53%
“…The groups allowed high fat diets (diabetic groups) had significantly higher blood glucose levels compared with the control and gliclazide groups. These differences in glucose level could be as a result of increased dietary intake (high fat diet), which often leads to obesity, insulin resistance and hyperglycaemia, as previously reported ( Lang et al, 2019 , Abi et al, 2020 ). There were further significantly increased blood glucose levels in the diabetic groups after induction with streptozotocin compared with the control and gliclazide groups, an indication that streptozotocin exacerbates hyperglycaemia.…”
Section: Discussionsupporting
confidence: 53%
“…The total caloric value of the diet was about 5340kcal/kg of which energy contribution of fat was about 70%. The fat component comprises of 60% saturated fat and 40% unsaturated fat (Abi et al, 2018).…”
Section: Compounded High Fat Diet Mealmentioning
confidence: 99%
“…Preventive groups (3,4,5) and Curative groups (6,7,8) studies in animals were done concurrently for 6 weeks. Rats, were randomly assigned to 9 groups consisting of 3 each as follows:…”
Section: Animal Groupingmentioning
confidence: 99%
See 1 more Smart Citation
“…The adoption of high fat diet (HFD) for induction of obesity, hyperglycemia and hyperlipidemia in experimental animals (especially mice) is gaining traction in recent literatures (Li et al, 2020). Our previous studies revealed that chronic HFD administration can cause hyperglycemia, heightened anxiety and memory impairment in mice (Abi et al, 2020;. High fat diet causes these, by some proposed mechanisms, such as the promotion of proinflammatory markers like IL-1, IL-6 and TNFα; activation of toll-like receptors and activation of protein-C causing inhibition of insulin-PI3K-Akt signaling (Duan et al, 2018;Wali et al, 2020).…”
Section: Introductionmentioning
confidence: 99%